Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

The work of a student to solve the equation 3(2x − 4) = 8 + 2x + 6 is shown below: Step 1: 3(2x − 4) = 8 + 2x + 6 Step 2: 5x − 7 = 14 + 2x Step 3: 5x − 2x = 14 + 7 Step 4: 3x = 21 Step 5: x = 7 In which step did the student first make an error and what is the correct step? (5 points) a Step 2; 6x − 12 = 14 + 2x b Step 2; 6x − 7 = 2(6 + x + 4) c Step 3; 5x − 2x = 14 − 7 d Step 3; 5x + 2x = 14 + 7

Sagot :

Step-by-step explanation:

The answer is 7x= 21

divide both sides by 7

to get 3

therefore the answer is X =3

We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.